(untitled) (Research, Society and Development, 2022)
Brazil presented different waves of contamination, registering different cases and numbers of deaths from COVID-19 depending on the region under study due to its continental size and territorial complexity, with 5,570 municipalities, 26 states, and one federal district. The focus of the study was to verify whether socioeconomic conditions have an influence on the pandemic and, if confirmed, to describe the mechanism and degree of influence. The study used a multivariate data analysis approach with a combination of exploratory factor analysis and hierarchical clustering techniques. The factor analysis resulted in the extraction of three factors with a characteristic root greater than one, which account for 94.23% of the total variation in the data, these being: basic assistance coverage; family assistance programs; basic education; and health care. In the cluster analysis, four differentiated groups were obtained from the factors listed. Among the main results, we highlight the fact that COVID-19 affected not only the health and epidemiological spheres in Brazil but also evidenced the existing social vulnerability, as well as generated impacts in different sectors.